2020
DOI: 10.1177/1356336x20957356
|View full text |Cite
|
Sign up to set email alerts
|

A one-year follow-up of basic psychological need satisfactions in physical education and associated in-class and total physical activity

Abstract: This study examined basic psychological need satisfactions for competence, autonomy, and social relatedness in physical education (PE) and their contributions to accelerometer-based in-class and total moderate to vigorous physical activity (MVPA) across a one-year follow-up (T1). Participants were 523 students (girls 280, boys 243; mean age = 11.26 ± 0.31) and the data were collected using self-reports and waist-worn accelerometers. The key findings were: (a) competence and social relatedness need satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…This coincides with that reported by Mitchell and Steele [ 53 ] and Tyler et al [ 54 ], who found that the majority of the population is physically active and largely avoids sedentary lifestyle habits. Grasten et al [ 55 ], Groffik et al [ 56 ], Petrie et al [ 57 ], and Reid et al [ 58 ] argue that physical activity engagement outside of school hours is encouraged by positive attitudes experienced in physical activity classes. In this sense, this prior research also outlined that the majority of students held positive attitudes towards the aforementioned subject.…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with that reported by Mitchell and Steele [ 53 ] and Tyler et al [ 54 ], who found that the majority of the population is physically active and largely avoids sedentary lifestyle habits. Grasten et al [ 55 ], Groffik et al [ 56 ], Petrie et al [ 57 ], and Reid et al [ 58 ] argue that physical activity engagement outside of school hours is encouraged by positive attitudes experienced in physical activity classes. In this sense, this prior research also outlined that the majority of students held positive attitudes towards the aforementioned subject.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results stress the importance of education, as teachers' encouragement of their students' autonomous motivation during PE is likely to persist in leisure time. Researchers have suggested that in order to improve students' outcomes, it is essential that all students receive positive and satisfying PE experiences (75). In order to identify the magnitude of the effect of support for autonomy t in PE on MVPA in PE, further interventional studies should be performed.…”
Section: Mediation Effectsmentioning
confidence: 99%
“…One of the main conclusions of this study is that, although it does not affect both genders equally, school satisfaction has a great positive association with life satisfaction. Therefore, it is essential that adolescents enjoy their classes and that their participation in the proposed tasks is perceived as positive and satisfactory [ 102 ]. According to the findings of this study, the association of school satisfaction with life satisfaction is especially pronounced in physical adolescents who do more PA, regardless of their age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the importance of physical activity is reinforced. From the perspective of PE, it is necessary to ensure that schoolchildren feel satisfied and motivated, since this is how they will perceive PE classes as pleasant and fun [ 103 ], which increases the possibilities of improving their present and future quality of life [ 102 ]. In fact, one of the great concerns for the World Health Organization [ 104 ] is precisely sedentary life, which is considered one of the greatest risk factors for people’s health, since it contributes to the decline in people’s quality of life, affecting the psychological level with the emergence of depressive conditions [ 105 ], causing dissatisfaction with life [ 106 ], and affecting the increase in overweight or obesity [ 32 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation